Optically excited nanoscale ultrasonic transducers - Smith, Richard J.; Cota, Fernando Perez; Marques, Leonel; Chen, Xuesheng; Arca, Ahmet; Webb, Kevin; Aylott, Jonathan W.; Somekh, Michael G.; Clark, Matt (Acoustical Society of America, 2015)
In order to work at higher ultrasonic frequencies, for instance, to increase the resolution, it is necessary to fabricate smaller and higher frequency transducers. This paper presents an ultrasonic transducer capable of being made at a very small size and operated at GHz frequencies. The transducers are activated and read optically using pulsed lasers and without physical contact between the instrumentation and the transducer. This removes some of the practical impediments of traditional piezoelectric architectures (such as wiring) and allows the devices to be placed immediately on or within samples, reducing the significant effect of attenuation which is very strong at frequencies above 1 GHz. The transducers presented in this paper exploit simultaneous optical and mechanical resonances to couple the optical input into ultrasonic waves and vice versa. This paper discusses the mechanical and optical design of the devices at a modest scale (a few lm) and explores the scaling of the transducers toward the sub-micron scale. Results are presented that show how the transducers response changes depending on its local environment and how the resonant frequency shifts when the transducer is loaded by a printed protein sample.